2011
DOI: 10.1017/s0025315411000385
|View full text |Cite
|
Sign up to set email alerts
|

Organic enrichment and structure of macrobenthic communities in the glacial Baker Fjord, Northern Patagonia, Chile

Abstract: In this study we describe community parameters such as densities, biomasses, species composition, feeding modes and normalized biomass size-spectra (NBSS) of macrobenthic invertebrate communities from three stations located in the Baker Fjord obtained on four seasonal campaigns in 2008 and 2009. The macrobenthic communities were dominated by small-bodied polychaetes (Paraonidae, Capitellidae and Cirratulidae) characterized by continuous year-round breeding, short life-spans, and fast turnover rates, which in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Horizontal, vertical and chemical stratification is found in the fjord habitats of southern Chile. The estuarine and benthic ecology of benthic populations is shaped by seasonal physical disturbances of natural origin that are associated with river discharge resulting from melting ice and the release of suspended particulate material (Vargas et al 2011, Quiroga et al 2012, Landaeta et al 2013, Zenteno et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Horizontal, vertical and chemical stratification is found in the fjord habitats of southern Chile. The estuarine and benthic ecology of benthic populations is shaped by seasonal physical disturbances of natural origin that are associated with river discharge resulting from melting ice and the release of suspended particulate material (Vargas et al 2011, Quiroga et al 2012, Landaeta et al 2013, Zenteno et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, our study supports the notion that quality rather than quantity of food determines the level of benthic productivity. As reported in numerous studies, sediment pigment concentration, which represents the 'freshly produced' fraction of organic matter in sediments and can be a measure of ecosystem productivity, was linked with higher biomass [51][52][53] . The relationship between δ 13 C and benthic standing stock is less obvious, especially in this study, where we reported higher standing stock in fjords characterized by lower δ 13 C values.…”
Section: Discussionmentioning
confidence: 80%
“…However, it must be noted that comparisons of intercept (treated as a proxy of total biomass) are only possible when spectra represent similar size class range (Hua et al 2013). The intercepts of NBSS plotted for Kongsfjorden fauna were higher than those reported by most other studies (Saiz-Salinas and Ramos 1999;Quiroga et al 2005Quiroga et al , 2012Quiroga et al , 2016, but similar to those of the communities inhabiting highly productive regions and sediments with high organic matter content (Akoumianaki et al 2006;Hua et al 2013). But it must be noted that these differences in intercepts may result from various sampling gears used and not overlapping size classes with our studies.…”
Section: Benthic Size Spectra Of An Arctic Fjordmentioning
confidence: 75%
“…The functioning of a system (e.g., productivity, rate of the energy flow through trophic levels) may be reflected in the size spectra characteristics. The intercept of NBSS can be an indicator of total biomass in the community (Sprules and Munawar 1986;Quiroga et al 2012) or a rate of primary production in the system in case of pelagic systems (Zhou 2006). However, it must be noted that comparisons of intercept (treated as a proxy of total biomass) are only possible when spectra represent similar size class range (Hua et al 2013).…”
Section: Benthic Size Spectra Of An Arctic Fjordmentioning
confidence: 99%
See 1 more Smart Citation